2019
DOI: 10.3390/mi10010062
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Field of Micro-Electrocorticography

Abstract: Since the 1940s electrocorticography (ECoG) devices and, more recently, in the last decade, micro-electrocorticography (µECoG) cortical electrode arrays were used for a wide set of experimental and clinical applications, such as epilepsy localization and brain–computer interface (BCI) technologies. Miniaturized implantable µECoG devices have the advantage of providing greater-density neural signal acquisition and stimulation capabilities in a minimally invasive fashion. An increased spatial resolution of the µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 126 publications
0
30
0
Order By: Relevance
“…Previous studies have reported a range of promising results regarding the possibility of building BCIs that employ ECoG recordings to enable motor functions. With the rapid developments in ECoG technologies (Shokoueinejad et al, 2019), surgical implantation procedures and mathematical algorithms for neural decoding, it is reasonable to expect that a variety of practical, fully-implantable (Vansteensel et al, 2016) ECoG-based neural prostheses will emerge for enabling motor and sensory functions to neurologically impaired patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a range of promising results regarding the possibility of building BCIs that employ ECoG recordings to enable motor functions. With the rapid developments in ECoG technologies (Shokoueinejad et al, 2019), surgical implantation procedures and mathematical algorithms for neural decoding, it is reasonable to expect that a variety of practical, fully-implantable (Vansteensel et al, 2016) ECoG-based neural prostheses will emerge for enabling motor and sensory functions to neurologically impaired patients.…”
Section: Discussionmentioning
confidence: 99%
“…As impedance is inversely proportional to recording site size but should be low as to decrease noise in recording [25,38]. In microelectrodes, where high impedance due to size can become a limiting factor, surface area is typically increased through roughening or functionalization [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Commercial ECoG electrodes (Ad-Tech Medical Instrument Corporation, USA), with millimeter electrode diameters (typically 2–3 mm) and pitches, are available to monitor cortical activity and locate the seizure focus during surgical diagnosis [ 13 , 14 ]. In the last decade, in order to obtain higher spatial resolution of cortical signals, there has been an evolution of ECoG into micro-electrocorticography (µECoG) by scaling down the dimensions of ECoG electrodes to micron size [ 15 ].…”
Section: Introductionmentioning
confidence: 99%